MASALAH PENGADAAN TANAH UNTUK PEMBANGUNAN PLTU DI BATANG - Achmad Taqwa Aziz (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The availability of land is important element in development activitiesespecially for public interest. This study aims todetermine the mechanisms applied in land acquisition for Batang Power Plant, in Batang, Central Java; and to explore the supportingand inhibiting supports in the implementation of the land acquisition and settlement efforts. This study explains development ofBatang Power Plant as infrastructure projects use the mechanism of Public Private Partnerships (PPP), according to The Law No. 30of 2009 on Electricity and Presidential Decree No. 13 of 2010. The supporting factors of the implementation of land acquisitionare existence of a positive perspective of residents, the price of the deal, the full support of government and large investmentfunds. The inhibiting factors of the implementation of the land acquisition are the attitude of the citizens of rejection, the pricedisagreement, the issue of environmental pollution and the emergence of land speculators. For resolving obstacles and constraintsin land acquisition created the establishment of a forum of communication together, increasing participation of citizens, transparencyand accountability, creating guarantees the survival of the farm laborers and tenants, and enhancing community empowermentthrough CSR programs.Keywords: Acquisition of land, the power plant.